Optimising processing conditions for the functionalisation of photocatalytic glazes by ZnO nanoparticle deposition - H.R. Guzmán-Carrillo (Consejo Superior de Investigaciones Científicas, 2021)
ZnO nanospheres were synthesised and then deposited by both single- and double-fire fast processes on as-prepared ceramic substrates. The photocatalytic degradation of resazurin ink was tested under UV light. The single-fired samples did not show any evidence of photocatalytic activity because the nanoparticles melted during sintering at 1210°C. The double-fire ZnO spray-coating method successfully produced glazed materials with an active ZnO surface layer despite the high sintering temperature. The influence of experimental parameters, including the ZnO nanoparticle loading (0.03 to 1 mg/cm2) and firing temperature (650 to 800°C), were also investigated. Samples with a ZnO loading of 1 g/cm2 fired at 650°C showed the best photocatalytic activity. Increasing the temperature to 700 and 800°C led to the coalescence of ZnO nanoparticles, which reduced the photocatalytic activity.